2018
DOI: 10.1037/dhe0000066
|View full text |Cite
|
Sign up to set email alerts
|

Added benefits: How supporting women faculty in STEM improves everyone’s job satisfaction.

Abstract: Can gender-based diversity programs benefit everyone? We tested whether and how a broadening participation program intended to benefit women working within maledominated academic fields of science, technology, engineering, and mathematics, may relate to job satisfaction for all who feel involved. Informed by self-determination theory (Deci & Ryan, 2012), we designed and tested a gender-diversity program that supported women faculty's psychological need for autonomy, relatedness, and competence through their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Three of these studies used a training intervention delivered directly to employees (Jungert et al, 2018; Pedersen et al, 2018, 2019; Williams et al, 2016) whereas Stenling and Tafvelin (2016) only examined the leader sample. One study did not use a training intervention and instead embedded need supports into the work design of the organization (Smith et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these studies used a training intervention delivered directly to employees (Jungert et al, 2018; Pedersen et al, 2018, 2019; Williams et al, 2016) whereas Stenling and Tafvelin (2016) only examined the leader sample. One study did not use a training intervention and instead embedded need supports into the work design of the organization (Smith et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…At post‐intervention, seven of the 10 studies concluded that the interventions yielded beneficial outcomes (Deci et al, 1989; Hardré & Reeve, 2009; Jungert et al, 2018; Pedersen et al, 2018, 2019; Smith et al, 2018; Stenling & Tafvelin, 2016; Williams et al, 2016). Two studies concluded that interventions showed relatively mixed findings (Forner, 2019; Yong et al, 2019), and one study concluded that there were no changes post‐intervention (Tafvelin et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…: -focus on the integration of employees (point 1 in the table), -respect for diversity (on the basis of sex, sexual orientation, disability, origin, ethnicity, age, etc.) (points 2,3,4,5 in the table), (Smith and co., 2018), -offering flexible forms of work (point 6 in the table), -information and access to knowledge about diversity (point 7 in the table) (Kompa and Witkowska, 2018). It can be seen from the above statements that in the analyzed periods the vast majority of companies / institutions undertakes activities aimed at the integration of employees (corporate events, integration trips, etc.…”
Section: Organizational Practices In the Field Of Diversity Managemenmentioning
confidence: 98%
“…The complex critical framework that undergirds the A&A Program directs explicit recognition of the harms of a gendered hierarchy for both men and women while simultaneously highlighting the benefits inherent in inclusive/diverse groups (Dailey-Hebert & Dennis, 2015;Kania & Kramer, 2013;Radford, 2008;Semetsky, 2008). This analysis reveals that men benefit from cultural and institutional changes that benefit women (J. L. Smith et al, 2017), and thereby provides a compelling path forward for addressing gender inequities.…”
Section: Theoretical Framework: a Complex Critical Analysismentioning
confidence: 99%